2006
DOI: 10.1002/cncr.22131
|View full text |Cite
|
Sign up to set email alerts
|

Oral outpatient chemotherapy medication errors in children with acute lymphoblastic leukemia

Abstract: BACKGROUND. Although medication errors are 1 of the most common types of medical errors, their frequency in pediatric patients receiving oral outpatient chemotherapeutic agents is unknown. The prescribing, dispensing, and parental administration of these medications to children receiving treatment for acute lymphoblastic leukemia (ALL) were systematically reviewed to determine the rate and types of medication errors occurring in these patients. METHODS. During a 2‐month study period, parents of children with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 19 publications
1
79
1
2
Order By: Relevance
“…17 Gandhi et al 15 found that 2% of pediatric oncology clinic visits and 3% of adult visits involved an error. Taylor et al 20 observed parents measuring chemotherapy in the clinic and found mistakes in 10%; we found fewer errors. By using medical record review, bottle review, and direct observation in the home, we were able to identify a broad range of error types that occur in outpatient pediatric oncology care.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…17 Gandhi et al 15 found that 2% of pediatric oncology clinic visits and 3% of adult visits involved an error. Taylor et al 20 observed parents measuring chemotherapy in the clinic and found mistakes in 10%; we found fewer errors. By using medical record review, bottle review, and direct observation in the home, we were able to identify a broad range of error types that occur in outpatient pediatric oncology care.…”
Section: Discussionmentioning
confidence: 42%
“…Other studies ask parents to demonstrate proper dosing of home medications while in the clinic. [20][21][22] These approaches assess only part of the entire process of home medication use and are subject to sampling bias. A comprehensive investigation of the spectrum of errors in medication use at home, assessing frequency and severity, is needed to identify vulnerabilities, target education, and design interventions.…”
mentioning
confidence: 99%
“…The rate of medication errors (4.5 per 100 medications) we found is consistent with those from prior studies of home medication use in children with cancer. 3,5 This project has several limitations. It occurred at a single site study and was designed to assess feasibility and parent satisfaction, not impact on error rates.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Home medication use in children with cancer is highly complex: doses change from day to day, liquids are difficult to measure, pills must be cut and crushed, and children with cancer take a median of 10 medications daily. 2,4 In a recent editorial, Landrigan et al called for more effective support for parents caring for ill children at home.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy error rates have been reported at 3%-16%. 14,15 Errors in ordering are most common, followed by administration and then dispensing. Missing or improperly written premedication orders prior to chemotherapy and missing treatment parameters could also lead to potentially serious adverse drug reactions.…”
mentioning
confidence: 99%